Influence of Work-Life Balance, Career Development, and Compensation on Generation Z’s Turnover Intentions in Surabaya - Virginia, Savira Vagantree; Ika Korika Swasti (International Journal of Economics and Management Sciences, 2025)
This study aims to analyze the influence of work life balance, career development, and Compensation  on turnover intention among Generation Z employees in Surabaya. The research used a quantitative method with a survey approach, distributing online questionnaires to 100 respondents who belong to Generation Z. Data were analyzed using the Partial Least Square (PLS) technique with the help of SmartPLS 3.0 software. The results show that work life balance, career development, and Compensation  have a negative and significant influence in reducing turnover intention. Generation Z employees who experience a balance between work and personal life, have career development opportunities, and receive adequate Compensation  tend to show higher loyalty to the company.